Edukasi Tanda dan Bahaya pada Kehamilan di Klinik Hj. Titiek Kota Makassa - Fatma Jama; Rahmawati Ramli; Wan Sulastri Emin; taqiyah, yusrah; Suhermi (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Maternal mortality rate (MMR) is an important indicator to see the importance of a nation's health status and is one of the components of the development index and quality of life index. Pregnancy danger signs are signs or symptoms that indicate the mother is in danger, based on the initial survey of the service team, getting data on the lack of knowledge of mothers about signs in pregnancy at the titiek Makassar field clinic. The purpose of this service is to provide education about danger signs in pregnant women. The method of service is by lecture / counseling, discussion and question and answer. The target respondents of the service were pregnant women who were in trimesters I, II, and III totaling 15 respondents. The results obtained after being given the material of the danger signs of pregnancy obtained the number of pregnant women who have good knowledge as many as 14 people (93.5%), and sufficient knowledge 1 person (6.5%). The conclusion of this service is that there is a good effect of counseling on pregnancy danger signs on pregnant women.